Building a Just Law: The Role of Legal Professional Ethics in Indonesia - Muttaqien, Muhammad Syahrul; Yubaidi, Ahmad; Abdulah Pakarti, Muhammad Husni; Husain; Hassan Bello, Abdulmajeed Bolade (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The professionalism of a legal professional is not only due to being competent, intellectual and successful in his field as a law enforcement officer, but the behavioral aspect is also part of the assessment that must be had in implementing the Code of Ethics or Legal Professional Ethics to uphold law and justice. However, if we look at the existing reality, there are still many legal practitioners who do not comply with the Code of Ethics for the Legal Profession. The research method in this journal uses normative juridical, which uses library-based secondary data sources. The results of this research are that the Code of Ethics for the Legal Profession must be obeyed (forced) even if it is not officially used as a regulation. Because Legal Professional Ethics has an important role in law enforcement which is also a manifestation of efforts to realize better law.